Altitude training for enhanced athletic performance - Noakes, T. D. (International SportMed Journal, 2000)
Many elite athletes believe that training at altitude improves sea level performance. Yet the scientific evidence, such as it is, would seem to refute this, suggesting that the athlete`s trust may be misplaced. However, these scientific studies do not exclude the possibility that altitude training might produce an effect (<1%) that is too small to be detected by current research methods, but which might be of very real significance to the elite athlete for whom a much smaller effect would be sufficient to ensure an Olympic medal or a new world record. In contrast, living at altitude and training at or near sea level—the process known as "living hi and training low"—may produce larger, more easily measurable effects (>1.25%) in individual athletes. It is speculated that this benefit occurs only in those athletes (i) who mount an appropriate increase in renal erythropoeitin (EPO) production with an increase in red blood cell (RBC) mass and (ii) who are able to sustain a high training intensity (running velocity) when training at low altitude. Hence, this effect requires that athletes live at altitudes of at least 2,500 m and perhaps up to 4,000 m, and have adequate iron stores to sustain increased RBC production occasioned by the altitude-induced increase in EPO production. They need also to train at an altitude sufficiently low that they are able to train at velocities equivalent to those achieved during sea level competition. Hence, at present, elite athletes can be neither encouraged to, nor discouraged from, training at altitude. Individual experience, rigorously evaluated, is the sole method by which correct conclusions can be drawn for individual athletes. Even a 1% improvement in performance will not make a sub-elite athlete elite; hence, there is no reason to encourage sub-elite athletes to train at altitude.